THE DEVELOPMENT OF CURRICULUM BASED ON THE INTEGRATED INFORMATION-EDUCATIONAL ENVIRONMENT - Mikhail S. Gasparian (Открытое образование (Москва))
The article discusses the development of competence-oriented curriculum based on the requirements of the federal state educational standards. In this context, an attempt is made to formulate a general model of information-educational environment, and to develop on its basis the technology of curriculum generation.